Bioinformatics analysis of the prognostic value of NEK8 and its effects on immune cell infiltration in glioma. Issue 18 (10th August 2021) - Xiao, Meng; Du, Chaoyang; Zhang, Chuanbo; Zhang, Xinzhong; Li, Shaomin; Zhang, Dainan; Jia, Wang
Abstract: Glioma is the most common malignancy of the nervous system with high rates of recurrence and mortality, even after surgery. The 5‐year survival rate is only about 5%. NEK8 is involved in multiple biological processes in a variety of cancers; however, its role in glioma is still not clear. In the current study, we evaluated the prognostic value of NEK8, as well as its role in the pathogenesis of glioma. Using a bioinformatics approach and RNA‐seq data from public databases, we found that NEK8 expression is elevated in glioma tissues; we further verified this result by RT‐PCR, Western blotting and immunochemistry using clinical samples. Functional enrichment analyses of genes with correlated expression indicated that elevated NEK8 expression is associated with increased immune cell infiltration in glioma and may affect the tumour microenvironment via the regulation of DNA damage/repair. Survival analyses revealed that high levels of NEK8 are associated with a poorer prognosis; higher WHO grade, IDH status, 1p/19q codeletion, age and NEK8 were identified as an independent prognostic factor. These findings support the crucial role of NEK8 in the progression of glioma via effects on immune cell infiltration and suggest that it is a new prognostic biomarker.